Physical and Release Properties of Metronidazole Suppositories (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2023)
Purpose: A study was made of the effects of some bases and adjuvants on the physical and release properties ofmetronidazole suppositories with a view to providing more information for the optimization of the rectal formulationof metronidazole.Method: Suppositories (1g) containing 200mg of metronidazole each were prepared in witepsol(H15 and E75) and polyethylene glycol (PEG 2850 and 4650) bases, using different concentrations of Tween 80,sodium salicylate and methylcellulose as adjuvants. The setting time, solidification point and melting range of thesuppositories were determined, along with their crushing strength, disintegration time and the time for 80% ofmetronidazole to be released from the suppositories (t80).Results: The ranking of setting time for the suppositorieswas witepsol H15 > PEG 2850 > witepsol E75 > PEG 4650, while the ranking of solidification point, melting range,crushing strength, disintegration time and the time for 80% of metronidazole to be released from the suppositories(t80) was the reverse of that for setting time. Optimal concentrations of Tween 80 and sodium salicylate wereobserved for the suppository formulations. Using Kitazawa plots, all formulations showed two dissolution rateconstants, k1 and k2 intersecting at time t1, with formulations containing 5 to 20 % w/w of methylcelluloseexhibiting a third dissolution rate constant, k3 intersecting with k2 at time t2.Conclusion: The physical and releaseproperties of metronidazole suppositories are influenced considerably by the bases and adjuvants employed. Tween80 and sodium salicylate can probably be used to formulate only immediate-release suppositories whilemethylcellulose can be useful for sustained-release metronidazole suppositories. Some insight into these inferencescan be obtained from parameters derived from Kitazawa plots.